Research in UK universities: a tale of two subjects - Economics and Econometrics; and Business and Management Studies - Johnston, James; Reeves, Alan (European journal of higher education, 2020)
This paper explores the comparative performance of two subject areas (Units of Assessment - UOAs) in the UK national Research Assessment Exercises of 1992, 1996, 2001, 2008 and the Research Excellence Framework of 2014. The Units of Assessment are Economics and Econometrics; and Business and Management Studies. Given the wide range of disciplines in the Business and Management Studies UOA universities have the choice of submitting their economics and econometrics research either to it or to the Economics and Econometrics UOA. Over the period 1992-2014 the number of universities entering the Economics and Econometrics UOA declined significantly in contrast to the growth in the number entering the Business and Management Studies UOA. The reasons for this include the finding that university managers were more likely to tolerate poor performance (measured by internal and external gaps) in Business and Management Studies than in Economics and Econometrics. Considerable differences were found between old (pre-1992) and new (post-1992) universities, with Economics and Econometrics now solely the domain of old universities as new ones have withdrawn. In sharp contrast, Business and Management Studies has a good balance of old and new universities.